Sensory symptom profiles differ between trigeminal and thoracolumbar postherpetic neuralgia. (January 2018) - Rehm, Stefanie; Groβkopf, Moritz; Kabelitz, Maria; Keller, Thomas; Freynhagen, Rainer; Tölle, Thomas R.; Baron, Ralf
Abstract: Introduction: Animal experimental evidence suggests that mechanisms of pain generation and response to treatment differ between neuropathic pain in the cephalic and the extracephalic innervation territories. Objectives: The objective of the study was to examine whether in humans an identical peripheral painful neuropathy is associated with different pain qualities and sensory abnormalities in the face as compared with the thoracic region. Methods: We retrospectively analysed epidemiological and clinical data of 639 patients with postherpetic neuralgia (PHN) in the face and at the trunk who were collected within a cross-sectional cohort survey and compared the respective sensory symptom profiles captured with the painDETECT questionnaire. Results: Two hundred twenty-four patients suffered from trigeminal PHN and 415 from thoracolumbar PHN. There were no significant differences in sex-ratio, age, body mass index, and pain duration. Patients with trigeminal PHN were more often severely depressed. Anxiety and sleep scores were not different. The average pain intensity was slightly higher in thoracolumbar PHN than trigeminal PHN (visual analogue scale 5.0 vs 4.6). Postherpetic neuralgia in the thoracolumbar region showed significantly more intense burning sensations, allodynia, painful attacks, and significantly less prickling and numbness than PHN in the face. Conclusions: The differences in sensory symptom profiles between facial PHN and truncal PHN might be associated with different pathophysiological mechanisms and different treatment response. Drugs that primarily act on sensitization processes in the peripheral nociceptive system may work better in thoracolumbar PHN than in trigeminal PHN. If new medications are tested in patients with PHN, it would therefore be of interest to include an analysis of the treatment results in regard to subgroups based on the localisation of pain in patients with PHN. Abstract : Differences in somatosensory profiles in different localisations in 1 distinct disease (postherpetic neuralgia) were shown. This might have implications for future research and treatment regimes.